Influence of spirituality, religiosity, and multicultural competency on counselors' self-efficacy in dealing with legal and ethical issues - Subarimaniam, Neerushah; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The researcher measured perceived spirituality, perceived religiosity, and perceived multicultural competency as the predictors of counselor’s self-efficacy in dealing with legal and ethical issues. The development and integration of values such as spirituality, religiosity, and multicultural competency have been mushrooming in a number of counseling field research areas such as career, family, and ethics. These values are viewed and accepted as important aspect in enhancing various dimensions of counselling practices. Spirituality is the sense of inter-connectedness with the Supreme Being and religiosity is defined as community and cultural beliefs that involves practices, rituals, and validation from a group of people. Multicultural competency is one’s awareness, knowledge, and skills about various cultures. The purpose of this study will be to examine the influence of spirituality, religiosity, and multicultural competency on counselors’ self-efficacy in dealing with legal and ethical dilemmas. The respondents will be trainee- counselors who will need to answer a set of questionnaires consisting of five components: demographic background, perceived spirituality, perceived religiosity, perceived multicultural competency, and self-efficacy in dealing with ethical issues. This study will use descriptive statistics to provide basic information retrieved from the data such as mean, mod, and median as well as Pearson Correlation to examine the relationship between the values and finally, multiple regressions to determine the values that influence counselor’s self-efficacy in dealing with ethical issues. The variable that has greatest influence on counselors’ self-efficacy will be identified at the end of data analysis.